THE CONTRIBUTION OF THE AUTOMATED SHORT ESSAY SCORING (ASES) ASSESSMENT MODEL IN THE FORMATION OF STUDENTS’ AKHLAKUL KARIMAH - Susilawati, Evi; Kahira, Imamul; Nurzannah, Nurzannah; Hanum, Latifah; Fitriana, Sheila (Hijri, 2023)
The decline in morals as a result of the development of the times and technology which is so rapid has an impact on changes in the morals of students. In higher education, students often commit plagiarism and copy the answers of their peers in taking exams. This condition certainly affects the Akhlakul Karimah of students, especially in their academic integrity. Basically, the formation of student morals can be corrected early on and controlled permanently through assessment activities carried out in learning activities. Permanent control can be carried out through the Automated Short Essay Scoring (ASES) assessment model. The ASES assessment model is an assessment model by automatically scoring essays by making assessments based on the similarity of students' answers so they cannot plagiarize and copy other people's answers. Given the importance of the ASES study model for the formation of the Akhlakul Karimah of students,  the purpose of this study is to determine the contribution of the Automated Short Essay Scoring (ASES) assessment model in the formation of Akhlakul Karimah students in the Business Ethics in Islam course. This research is a Class Action Research  (CAR) used model John Elliot and is carried out in 3 cycles, where each cycle consists of  stages, namely: planning, action, observating, and reflection. The research instruments used in this study were lecturer and student observation sheets and student test sheets. The results showed that Automated Short Essay Scoring contributed to the formation of Akhlakul Karimah students in the Business Ethics in Islam course which can be seen from the average grades of cycles 1, 2 and 3 of 68.15, 77.85, and 83.90.Keywords: Assessment Model, Automated Short Essay Scoring (ASES), Akhlakul Karimah